BÜTÜN YÖNLERİYLE HOCALI SOYKIRIMI - Veliyev, Cavid (Fırat University, 2013)
1918 yılına kadar Türk toprağı olan ve hatta kurulduğu dönemde nüfusunun yarısı Türk olan Ermenistan Cumhuriyeti topraklarında bugün bir tane bile Türk yaşamamaktadır. Fakat bugün Türk devletlerinde on binlerce Ermeni yasal ve yasa dışı yollarla yaşamaktadır. Ermenistan Cumhuriyeti topraklarını Türkler’den arındırma süreci planlı bir şekilde 1800`li yılların başından başlamış, 1918-1920, 1945–1946 ve 1988 yılında devam etmiştir. Bu süreç Türklerin Ermenistan’ın toprak bütünlüğüne saygı duyduğu, hiçbir yabancı güçle işbirliği yapmadığı ve hiçbir ayrılıkçı eylem yapmadığı bir dönemde yaşanmıştır. Türkler zamanında topraklarını paylaştıkları Ermeniler1 tarafından kovulmuş ve kovulma sıradan bir kovulma olmamıştır.

People of South Caucasus have suffered from the expansionist of regional powers such as Russia, Iran and Ottoman Imperia. After the Tsarist Russia took control over the South Caucasus it has implemented “divide et impera” principle over the region. Under this principle, Russia generally used region peoples against each other. At the same time some people of the region had closer relations with Tsarist Imperia in response Russia’s favorable and wardship attitude in order to reach their objectives. This situation entailed conflict amongst regional nations. Armenians with the help of Tsarist Russia began expansionist regional policy and this policy has been continued throughout XX century as well. Khojaly is an essence of Armenian expansionism. Karabakh war began in 1988 by Armenia. Armenia claimed Karabagh and began attack not only Karabakh Azerbaijanis and also against Azerbaijanis those lived in Armenia. From 1991 that war transformed ethnic cleansing and genocide against civil people that lived in Karabagh. These actions and policies had objective to make Azerbaijani people afraid of repeating Khojaly, not to give permission them come back and to open new stage in order to occupy Azerbaijan territories. Armenians with the support of 366 Brigade of former Soviet Union implemented genocide in Khojaly. First days generally it was to difficult to convince international community about that genocide. However fortunately international community has started to recognize Khojaly as a genocide